Antagonistic roles of abscisic acid and cytokinin during response to nitrogen depletion in oleaginous microalga Nannochloropsis oceanica expand the evolutionary breadth of phytohormone function. (28th August 2014) - Lu, Yandu; Tarkowská, Danuše; Turečková, Veronika; Luo, Tingwei; Xin, Yi; Li, Jing; Wang, Qintao; Jiao, Nianzhi; Strnad, Miroslav; Xu, Jian
Summary The origin of phytohormones is poorly understood, and their physiological roles in microalgae remain elusive. Genome comparison of photosynthetic autotrophic eukaryotes has revealed that the biosynthetic pathways of abscisic acid (ABA) and cytokinins (CKs) emerged in unicellular algae. While ABA and CK degradation mechanisms emerged broadly in algal lineages, complete vascular plant‐type conjugation pathways emerged prior to the rise of Streptophyta. In microalgae, a complete set of proteins from the canonical ABA and CK sensing and signaling pathways is not essential, but individual components are present, suggesting stepwise recruitment of phytohormone signaling components. In the oleaginous eustigmatophyte Nannochloropsis oceanica IMET1, UHPLC‐MS/MS detected a wide array of plant hormones, despite a phytohormone profile that is very distinct from that of flowering plants. Time‐series transcriptional analysis during nitrogen depletion revealed activation of the ABA biosynthetic pathway and antagonistic transcription of CK biosynthetic genes. Correspondingly, the ABA level increases while the dominant bioactive CK forms decrease. Moreover, exogenous CKs stimulate cell‐cycle progression while exogenous ABA acts as both an algal growth repressor and a positive regulator in response to stresses. The presence of such functional flowering plant‐like phytohormone signaling systems in Nannochloropsis sp. suggests a much earlier origin of phytohormone biosynthesis and degradation than previously believed, and supports the presence in microalgae of as yet unknown conjugation and sensing/signaling systems that may be exploited for microalgal feedstock development.